Peningkatan Kecerahan Warna Ikan Molly (Poecilia sphenops) melalui Penambahan β-Karoten dari Ekstrak Kulit Buah Kelapa Sawit (Elaeis guineensis) pada Pakan - Muhazzir, Said; Mutakin, Abdul; Thaib, Azwar; Sabil, Shahrul Rajab; Handayani, Lia (Jurnal TILAPIA, 2025)
Decline in body coloration intensity in molly fish (Poecilia sphenops) is a common issue in ornamental fish aquaculture, primarily caused by a reduction in pigment concentration. Carotenoids, particularly β-carotene, are known to enhance fish coloration. Oil palm (Elaeis guineensis), especially its mesocarp, contains significant amounts of β-carotene and has potential as a natural source of pigment in fish feed. This study aimed to evaluate the effect of β-carotene extract derived from oil palm on the color intensity of molly fish and to determine the optimal dosage for improving color quality. A non-parametric Completely Randomized Design (CRD) was employed, consisting of four treatments with two replications: A (0% β-carotene), B (10% β-carotene), C (20% β-carotene), and D (30% β-carotene). Molly fish used in the study had an initial average Total Color Fidelity (TCF) score of 16, with a stocking density of six fish per aquarium. The main parameter observed was the increase in color brightness. Results indicated that the addition of β-carotene extract significantly enhanced the color intensity of the fish, with treatment D (30% β-carotene) yielding the highest improvement, reaching an average TCF score increase of 18.33 points. In conclusion, supplementation of oil palm-derived β-carotene extract in the diet effectively improves the coloration of molly fish, with 30% β-carotene identified as the optimal dosage for achieving significant color enhancement.